Analisis Tundaan Kendaraan Akibat Weaving Di Jalan Diponegoro Menggunakan Metode Gap Acceptance - Desviolla, Millennia Yessy; Putra, Sasana; Ofrial, Siti Anugrah Mulya Putri; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2024)
The slowing down of vehicle speed that occurs on Jalan Diponegoro is caused by the behavior of vehicles that make intertwining movements (weaving). This condition causes vehicles traveling straight to reduce vehicle speed due to the presence of vehicles entering from Jalan Dr. Cipto Mangunkusumo towards Jalan Diponegoro. Queues that occur on Jalan Diponegoro cause a narrowing of the road, which can cause travel delays. The aim of this research is to analyze travel delays due to interwoven conflicts or weaving that happened on Jalan Diponegoro. This research was analyzed using the method gap acceptance. According to the results of data processing analysis and literature studies, the delay time was 23.28 seconds in the morning and 13.77 seconds in the afternoon for each 5 minute time interval. Key words: Travel Delay, InterwovenConflict, Gap Acceptance.